Molecular mechanisms of structural relaxation of DNA kinks - Shashel, Y. V.; Tolstorukov, M. Ye. (Biophysical Bulletin, 2006)
Molecular dynamics simulation and comparative analysis of the naked DNA structure and the DNA structure from purine repressor-DNA complex have been performed to study possible mechanisms of the relaxation of the deformations imposed on DNA in the complex, specifically, DNA kinking. The time evolution of both dinucleotide step parameters and the parameters that describe duplex configuration at higher levels (minor and major groove widths, end-to-end distance, etc) were analyzed. It was shown that the relaxation of the dinucleotide step kink occurs step-wise during relatively short time intervals. At the same time, such kink relaxation does not result in the straightening of the entire duplex; rather the bend is redistributed between several neighboring steps and the duplex remains in the bent configuration. The relaxation of the entire duplex occurs continuously and requires noticeably larger times. Thus, the obtained results allow us to conclude that the structural relaxation of the kink deformation imposed on DNA duplex occurs in stages, which are associated with different time scales.